In vivo study of cherry stick effect on concentration of serum total cholesterol, triglyceride and total protein in white albino male mice - Najeeb M. Saleem, Maysoon M.; Mohammad, Arieg A.W.; Al-Amiery, Ahmed A. H.; Hussan, Yasmin K. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Cherry extract has a wide range of biological activity. In the present investigation, two oral doses 0.04&0.08 mg/kg/day of cherry stick (ethanol extract) in albino male mice resulted in a significant decrease in concentration of serum total cholesterol concentration, triglyceride and total protein, albumin and globulin.Objective: we investigated the impact of biological activities of cherry stick extract on serum cholesterol, triglyceride, total protein, albumin and globulin in white albino male mice.Design: This study include three groups of white albino male mice. The first group (G1) was a control group comprised of 5 animals. The second group (G2) consisted of 5 animals treated with 1ml of cherry stick extract at concentration of 0.04 mg/kg/day for two weeks after treatment, while the third group (G3) consists of 5 animals treated with 1ml of cherry stick extract at concentration of 0.08 mg/kg/day for two weeks with treated animals.Results: there was a statistically significant reducing effect on serum total cholesterol, triglyceride, total protein and albumin P